2017
DOI: 10.1016/j.celrep.2017.05.087
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Proliferation of Human Cancer Cells with Ever-Shorter Telomeres

Abstract: Acquisition of replicative immortality is currently regarded as essential for malignant transformation. This is achieved by activating a telomere lengthening mechanism (TLM), either telomerase or alternative lengthening of telomeres, to counter normal telomere attrition. However, a substantial proportion of some cancer types, including glioblastomas, liposarcomas, retinoblastomas, and osteosarcomas, are reportedly TLM-negative. As serial samples of human tumors cannot usually be obtained to monitor telomere le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
100
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 60 publications
(73 reference statements)
13
100
0
Order By: Relevance
“…4C). This observation supports recent reports indicating that a subset of metastatic tumors, including melanomas and neuroblastomas could have progressed towards metastasis without activating a telomere maintenance mechanism (48,49). On the contrary, our most striking result is that telomerase activation and ATRX mutations do impact the prognosis, particularly in the group at high risk of progression (cluster C1A).…”
Section: Discussionsupporting
confidence: 92%
“…4C). This observation supports recent reports indicating that a subset of metastatic tumors, including melanomas and neuroblastomas could have progressed towards metastasis without activating a telomere maintenance mechanism (48,49). On the contrary, our most striking result is that telomerase activation and ATRX mutations do impact the prognosis, particularly in the group at high risk of progression (cluster C1A).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a recent survey of 6835 cancers showed that 22% of tumors neither express telomerase at detectable level nor harbored characteristics of ALT 65 . In line with this unexpected observation, cases of metastatic melanoma cells 66 and high-risk neuroblastoma 67 have been reported that lacked significant canonical telomere lengthening mechanisms. We propose that unleashed SCR might constitute the first step in bypassing the proliferation barrier induced by unprotected telomeres during carcinogenesis, before full telomere stabilization takes place via either telomerase reactivation or ALT.…”
Section: Discussionmentioning
confidence: 63%
“…The extreme initial telomere length of ALT cells and the relatively low rate of expected telomere erosion due to the end replication problem can explain this finding. As a result, U2OS cells lacking PML or the BTR complex resemble the phenotype seen in certain tumors that lack any form of telomere maintenance, termed ever-shorter telomeres (Dagg et al 2017). This suggests that, within ALTpositive tumors, the pressure to sustain ALT activity may be lost in cells with extremely elongated telomeres.…”
Section: Discussionmentioning
confidence: 99%